(Invited) Baseplate Materials for Securing Reliability of Wide Band Gap Power Semiconductor Module Operating at High Temperatures. (21st September 2015) - Takahashi, Hiroki; Anzai, Takeshi; Kato, Fumiki; Sato, Shinji; Tanisawa, Hidekazu; Murakami, Yoshinori; Watanabe, Kinuyo; Sato, Hiroshi
Abstract : Baseplate material properties for realizing high temperature resistant power modules are investigated. Power modules should have a tolerance for heavy thermal cycle load and retain their original performance. Therefore, it is important to improve the reliability of the heat dissipation path, which is the soldered joint between the baseplate and ceramic substrate. This study aimed to improve reliability by appropriately selecting the baseplate material and relaxing the thermal stress in the soldered joint. We conducted a series of verification tests using four types of baseplate material. Our results clarified that a smaller mismatch of coefficient of thermal expansion (CTE) between the baseplate and ceramic substrate contributes to an improvement in reliability, especially in case of W–Cu as the baseplate material. Conversely, the results also clarified that baseplate plastic deformation contributes to an improvement in reliability even if the CTE mismatch is large, in the case of Al.